Rola pielęgniarki w opiece nad pacjentem z atopowym zapaleniem skóry = Nurse’s role in taking care of a patient with atopic dermatitis - Filipska, Karolina; Zalewska, Iwona; Ciesielska, Natalia; Sokołowski, Remigiusz; Podhorecka, Marta; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Filipska Karolina, Zalewska Iwona, Ciesielska Natalia, Sokołowski Remigiusz, Podhorecka Marta, Zukow Walery. Rola pielęgniarki w opiece nad pacjentem z atopowym zapaleniem skóry = Nurse’s role in taking care of a patient with atopic dermatitis. Journal of Education, Health and Sport. 2016;6(1):229-240. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45344 http://ojs.ukw.edu.pl/index.php/johs/article/view/3357 https://pbn.nauka.gov.pl/works/710179 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 25.01.2016. Rola pielęgniarki w opiece nad pacjentem z atopowym zapaleniem skóry Nurse’s role in taking care of a patient with atopic dermatitis Karolina Filipska1, Iwona Zalewska1, Natalia Ciesielska1, Remigiusz Sokołowski2, Marta Podhorecka1, Walery Zukow3 1Katedra i Klinika Geriatrii, Uniwersytet Mikołaja Kopernika Collegium Medicum, Bydgoszcz 2Katedra Higieny, Epidemiologii i Ergonomii, Zakład Ergonomii i Fizjologii Wysiłku Fizycznego, Uniwersytet Mikołaja Kopernika Collegium Medicum, Bydgoszcz 3Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: atopowe zapalenie skóry, psychologiczne aspekty chorób, świąd, rola pielęgniarki. Keywords: atopic dermatitis, psychological aspects of diseases, itching, nurse’s role. Streszczenie Wstęp. Atopowe zapalenie skóry (AZS, ang. atopic dermatitis) jest chorobą alergiczną o przewlekłym i nawracającym przebiegu. Toczący się proces chorobowy dotyczy naskórka i skóry właściwej. AZS to najpowszechniej występująca przewlekła choroba zapalna dzieci, której patogeneza nie jest do końca poznana. Uznaje się, że na rozwój choroby składają się czynniki genetyczne, immunologiczne, oraz środowiskowe. Cel. Przedstawienie roli pielęgniarki w opiece nad pacjentem z atopowym zapaleniem skóry. Materiał i metody. Dokonano przeglądu 43 doniesień naukowych – artykuły badawcze i poglądowe oraz literatura współczesna - obejmujących swą tematyką rolę pielęgniarki w opiece nad pacjentem z atopowym zapaleniem skóry. Posługując się słowami kluczowymi: atopowe zapalenie skóry, psychologiczne aspekty chorób, świąd rola pielęgniarki przeszukano bazy bibliograficzne Ebsco, ScienceDirect, SpringerLink, Medline. Wyniki. Zadania pielęgnacyjno-opiekuńcze wynikają z poszczególnych symptomów AZS. Wśród założeń opieki pielęgniarskiej wymienia się: zmniejszenie świądu i suchości skóry; zminimalizowanie zaburzeń sennych; obniżenie ryzyka wtórych nadkażeń bakteryjnych, wirusowych lub grzybiczych; oraz kompleksowa edukacja chorego i jego rodziny w celu szybszej rekonwalescencji i wydłużenia okresów remisji. Wnioski. AZS wpływa negatywnie na domenę fizyczną, psychiczną i społeczną chorego. Ze względu na swoją przewlekłość oraz szerokie rozpowszechnienie należy do jednego z największych wyzwań zarówno dla pielęgniarki jak i całego zespołu terapeutycznego. Skuteczne leczenie dermatologiczne, właściwa opieka pielęgnacyjna i psychologiczna, oraz edukacja powinny stanowić stały element kompleksowej opieki nad chorym z AZS. Summary Introduction. Atopic dermatitis (AD) is an allergic disease of chronic and recurrent course. Progressing disease refers to the epidermis and dermis. AD is the most commonly occurring chronic inflammatory disease of children, whose pathogenesis is not fully understood. It is recognized that the development of the disease consists of genetic, immunologic, and environmental factors. Purpose. Presentation of the role of nurses in the care of patients with atopic dermatitis. Materials and methods. A review of 43 scientific reports - research articles and opinion articles and contemporary literature - including its theme the role of nurses in the care of patients with atopic dermatitis. Using the key words: atopic dermatitis, psychological aspects of the disease, pruritus, the role of nurses searched bibliographic databases EBSCO, ScienceDirect, SpringerLink, Medline. Results. The tasks of nursing care stem from individual symptoms of AD. Among the objectives of nursing care are: reducing itching and dry skin; minimizing distortions dream; reducing the risk of Second bacterial, viral or fungal infections; and comprehensive education of the patient and his family for faster recovery and longer periods of remission. Conclusions. AD domain negatively affects physical, mental and social of the patient. Due to its excessive length and wide dissemination is one of the biggest challenges for both the nurses and the entire therapeutic team. Effective treatment of dermatological, proper home care and psychological care, and education should be a regular part of comprehensive care for patients with AD.